LITERATURE ANALYSIS ON THE STUDY OF THE PHYSIOLOGY OF THE COTTON PLANT (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This article provides information on the physiological characteristics of the cotton plant, analysis of studies on the use of species, botanical description, characteristics, and cultivation technology